Birthdating of myenteric neuron subtypes in the small intestine of the mouse. Issue 3 (15th February 2014) - Bergner, Annette J.; Stamp, Lincon A.; Gonsalvez, David G.; Allison, Margaret B.; Olson, David P.; Myers, Martin G.; Anderson, Colin R.; Young, Heather M.
ABSTRACT There are many different types of enteric neurons. Previous studies have identified the time at which some enteric neuron subtypes are born (exit the cell cycle) in the mouse, but the birthdates of some major enteric neuron subtypes are still incompletely characterized or unknown. We combined 5‐ethynynl‐2′‐deoxyuridine (EdU) labeling with antibody markers that identify myenteric neuron subtypes to determine when neuron subtypes are born in the mouse small intestine. We found that different neurochemical classes of enteric neuron differed in their birthdates; serotonin neurons were born first with peak cell cycle exit at E11.5, followed by neurofilament‐M neurons, calcitonin gene‐related peptide neurons (peak cell cycle exit for both at embryonic day [E]12.5–E13.5), tyrosine hydroxylase neurons (E15.5), nitric oxide synthase 1 (NOS1) neurons (E15.5), and calretinin neurons (postnatal day [P]0). The vast majority of myenteric neurons had exited the cell cycle by P10. We did not observe any EdU+/NOS1+ myenteric neurons in the small intestine of adult mice following EdU injection at E10.5 or E11.5, which was unexpected, as previous studies have shown that NOS1 neurons are present in E11.5 mice. Studies using the proliferation marker Ki67 revealed that very few NOS1 neurons in the E11.5 and E12.5 gut were proliferating. However, Cre‐lox‐based genetic fate‐mapping revealed a small subpopulation of myenteric neurons that appears to express NOS1 only transiently. Together, our results confirm a relationship between enteric neuron subtype and birthdate, and suggest that some enteric neurons exhibit neurochemical phenotypes during development that are different from their mature phenotype. J. Comp. Neurol. 522:514–527, 2014. © 2013 Wiley Periodicals, Inc.